Analysis of the dissemination index of the information of the different players of the entrepreneurial ecosystem in the Valencian community - Gabriela Ribes-Giner; Javier Navarrete-Garnes (Administrative Sciences, 2020)
The main objective of this research is to calculate the diffusion index of entrepreneurship to the different actors of the entrepreneurial ecosystem. For this, 57 organizations, both private and public, belonging to the entrepreneurial ecosystem of the Valencian community have been analyzed. Among the results are stresses the importance of the optimal use of information and communication technology in current and future generations, as well as the dissemination of entrepreneurship. In addition, the best practices carried out by the different agents of the entrepreneurial ecosystem have been identified.
Keywords: 350; dissemination index; entrepreneurship; entrepreneurial ecosystem; diffusion; Valencian community